PENGARUH TEKNOLOGI INFORMASI KOMUNIKASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI PADA RSUD SULTAN ISKANDAR MUDA - Arwin, Arwin; Ansari, Ansari (Fakultas Ekonomi, 2024)
This study aims to determine the influence of information and communication technology and job satisfaction on organizational commitment among employees of Sultan Iskandar Muda General Hospital. This study is a quantitative study using primary data in the form of a questionnaire for data collection, and secondary data in the form of literature studies. The population in this study was all employees working at Sultan Iskandar Muda General Hospital, totaling 163 employees. The sample was taken using the Slovin technique of 116 employees, using a purposive sampling technique. The data analysis technique in this study was using multiple linear regression analysis with first conducted validity and reliability tests. To see whether there is an influence between the independent and dependent variables partially, a t-test was used. The results of the multiple linear regression analysis data processing indicate that there is a positive influence of information and communication technology and job satisfaction on organizational commitment both partially and simultaneously.